Pilkada Serentak Sebagai Sarana Mencari Pemimpin Yang Komunikatif - Kholid Kholid (Universitas Islam Darul Ulum Lamongan, 2021)
Direct regional head elections are also included in Law no. 32 Article 56 paragraph 1 concerning Regional Government which states that Regional Heads and Deputy Regional Heads are elected in a pair of candidates which are carried out democratically based on the conditions that democratic elections are elections that are run free and fair (Asfar, 2002: 12). The existence of universal suffrage for adults, meaning that every adult citizen has the right to vote and be elected, second, fairness of voting. There is a fair or just election process. To measure whether an election is run fairly and fairly, the principles of Luber and Justice. Third, there is a special right for political parties to organize and nominate candidates so that voters have many choices to choose between different candidates, both in groups and programs. The success of an organization in achieving its goals cannot be separated from the quality of its leaders. Both private organizations and leaders' public organizations are a necessity. The importance of a leader is at least because first, as a determinant of the direction the organization wants to take to achieve its goals and various goals. Second, mediators, especially in overcoming conflicts that may arise between individuals in a work group and between work groups in the organization they lead. When, integrators, are rational and objective. Fourth, an effective communicator and as a representative of an organization when dealing with outside parties. With various problems and challenges Direct elections for political parties must actually carry out open recruitment because this is one of the conditions for upholding democratic principles. Recruitment is open, meaning that any citizen who has quality indiscriminately has the same right to become a candidate for regional head even though he lacks capital. Unlike now where candidates for regional heads are dominated by people who have large capital, but quality measures are numbered behind. As a consequence, political parties must facilitate regional head candidates to obtain funds so that communicative leaders will be born who are not held by group interests, especially political parties.